DAYA SAING DAN MODEL PEMASARAN SENTRA INDUSTRI USAHA KERAJINAN SANGKAR BURUNG PERKUTUT - Diah Arum Savitri; Ujang Sumarwan; Bagus Putu Yudhia Kurniawan (School of Business, Bogor Agricultural University (SB-IPB), 2014)
ABSTRACTThe objectives of this study were 1) analyzing the competitiveness, 2) analyzing the market size, 3) analyzing marketing strategies’ priorities and alternatives to improve the competitiveness of industry center of dove cage in Dawuhan Mangli Village, Jember Regency. The method used in this study was descriptive analysis. The analysis tools used in this study were Porter’s Diamond Theory, BCG (Boston Consulting Group), SWOT and AHP (Analytical Hierarchy Process). Competitiveness analysis using diamond theory of Porter showed that industry center of dove cage handicraft in Dawuhan Mangli Village, Jember Regency is still weak. There are 9 components that have weaknesses while other 7 components have strengths. Market growth rate and relative market share formulated on BCG diagram are in the position of Question Marks, which means that the business has the opportunity to grow and expand but needs sufficient cash flow in order to increase its relative market. Based on SWOT and AHP analysis were obtained 7 marketing strategies with their priorities scales including: strengthening the capital, PSBP group formation, education and training, warehouse and workshop building, institutional formation of marketing and raw materials, increasing promotion, improving the quality and diversification of products. To enhance the industrial competitiveness of dove cage industry, development activities through strengthening the marketing and raw materials institution should be done.Keywords: competitiveness, marketing strategy, dove cage ABSTRAKTujuan penelitian ini adalah 1) menganalisis daya saing, 2) menganalisis market size, 3) merumuskan prioritas strategi pemasaran untuk sentra industri usaha kerajinan sangkar burung perkutut di Desa Dawuhan Mangli, Kabupaten Jember. Metode yang digunakan adalah analisis deskriptif. Analisis yang digunakan adalah Porter’s Diamond Theory, analisis BCG (Boston Consulting Group), SWOT, dan AHP (Analytical Hierarchy Process). Analisis daya saing menggunakan teori berlian dari porter menunjukkan daya saing sentra industri kerajinan sangkar burung perkutut Desa Dawuhan Mangli Kabupaten Jember masih lemah. Terdapat sembilan komponen yang memiliki kelemahan, sedangkan tujuh komponen memiliki kelebihan. Tingkat pertumbuhan pasar dan bagian pasar relatifnya yang di formulasikan pada diagram BCG berada pada posisi Question Marks artinya bisnis ini memiliki peluang untuk tumbuh dan berkembang tetapi diperlukan aliran kas yang cukup agar dapat meningkatkan pasar relatifnya. Hasil analisis SWOT dan AHP didapatkan tujuh strategi pemasaran dengan skala prioritasnya antara lain: memperkuat permodalan, pembentukan kelompok PSBP, pendidikan dan pelatihan, pembuatan gudang dan workshop, pembentukan kelembagaan pemasaran dan bahan baku, meningkatkan promosi, meningkatkan kualitas dan diversifikasi produk. Dalam meningkatkan daya saing industri usaha kerajinan sangkar burung perkutut dibutuhkan pengembangan aktivitas melalui penguatan pengembangan kelembagaan pemasaran dan bahan baku. Kata kunci: daya saing, strategi pemasaran, sangkar burung perkutut, Jember